Muslim exegesis of the Bible in medieval Cairo : Najm al-Din al-Tufi's (d. 716/1316) commentary on the Christian scriptures - Ṭūfī, Sulaymān ibn ʻAbd al-Qawī, 1259?-1316. (The History of Christian-Muslim Relations, 2013)
Najm al-Dīn al-Ṭūfī's (d. 716/1316) extraordinary commentary on the Christian scriptures has not received the scholarly attention it deserves. Illustrating the way in which the Bible was read, interpreted and used as a proof-text in the construction of early 14th century Muslim views of Christianity, his al-Ta'līq 'alā al-Anājīl al-arba'a wa-al-ta'līq 'alā al-Tawrāh wa-'alā ghayrihā min kutub al-anbiyā' (Critical Commentary on the Four Gospels, the Torah and other Books of the Prophets) is an invaluable treasure for the study of Muslim-Christian dialogue and its history. In Muslim Exegesis of the Bible in Medieval Cairo, Lejla Demiri makes this important and unusual work available for the first time in a scholarly edition and English translation, with a full introduction that places Ṭūfī in his intellectual context.